10-Year Outcome of Complete or Infarct Artery-Only Revascularization in STEMI With Multivessel Disease: The DANAMI-3-PRIMULTI Study - Marquard, Jasmine M; Beske, Rasmus P; Kelbæk, Henning; Holmvang, Lene; Pedersen, Frants; Clemmensen, Peter; De Backer, Ole; Raungaard, Bent; Eftekhari, Ashkan; Islam, Utsho; Køber, Lars; Tilsted, Hans-Henrik; et al. (Journal of the American College of Cardiology, 2025)
The long-term outcomes of complete revascularization in ST-segment elevation myocardial infarction (STEMI) and multivessel disease is unknown. The purpose of this study was to investigate the 10-year clinical outcomes including repeated events of fractional flow reserve (FFR)-guided complete revascularization vs treatment of the infarct-related artery only in STEMI. This 10-year follow-up study of DANAMI-3-PRIMULTI (Third DANish Study of Optimal Acute Treatment of Patients With STEMI-Complete Revascularization versus Infarct-Related Artery Only) included patients with STEMI and ≥1 angiographically significant non-infarct-related lesion, randomized to FFR-guided complete revascularization or infarct-related artery only after the index procedure. As the original trial, the primary outcome was a composite of all-cause mortality, recurrent myocardial infarction, or any revascularization. Repeated events of revascularization and myocardial infarction were analyzed. Of 627 included patients, 313 were randomized to infarct-related artery only and 314 to complete revascularization. After 10 years, complete revascularization reduced the risk of the primary outcome (HR: 0.76; 95% CI: 0.60-0.94; P = 0.014). In the infarct-related artery-only group, 78 (25%) died vs 74 (24%) in the complete revascularization group. Complete revascularization reduced any revascularization compared with infarct-related artery only (OR: 0.62; 95% CI: 0.44-0.89). There was no difference in recurrent myocardial infarction (OR: 0.90; 95% CI: 0.60-1.35). The mean cumulative number of events were 76 per 100 persons (95% CI: 66-88) in the infarct-related artery-only group vs 63 events per 100 persons (95% CI: 54-73) in the complete revascularization group (absolute reduction: 13%; 95% CI: -1% to 28%). FFR-guided complete revascularization reduced future and repeated events compared with infarct-related artery only after 10 years. The risk was mainly driven by revascularization, with no reduction in myocardial infarctions or death. (Primary PCI in Patients With ST-elevation Myocardial Infarction and Multivessel Disease: Treatment of Culprit Lesion Only or Complete Revascularization [PRIMULTI]; NCT01960933).